宝钢炼铁厂烧结炉用悬挂减速机国产化的改进设计 - 张立福; 王云恒 (Jixie chuandong)
The failure phenomenon of final stage large gear pitting,spalling and so on in the suspension reducer imported from Japan are summarized,and the system analysis is carried out.The localization optimization design is carried out from the gear material and heat treatment,improved the gear accuracy,improving processing technology and other aspects.